Safety of G-CSF with concurrent chemo-radiotherapy in limited-stage small cell lung cancer - Secondary analysis of the randomised phase 3 CONVERT trial. (March 2021) - Gomes, Fabio; Faivre-Finn, Corinne; Mistry, Hitesh; Bezjak, Andrea; Pourel, Nicolas; Fournel, Pierre; Van Meerbeeck, Jan; Blackhall, Fiona
Highlights: G-CSF use with cCTRT for small cell lung cancer is common despite safety controversy. No evidence of a causal effect between exposure to G-CSF and myelotoxicity. The use of G-CSF was not associated with toxic deaths or worse survival outcomes. G-CSF supported the cCTRT delivery by maintaining the treatment dose intensity. Abstract: Objectives: The use of granulocyte colony-stimulating factors (G-CSF) during concurrent chemo-radiotherapy (cCTRT) for small cell lung cancer is not recommended by the American Society of Clinical Oncology due to safety concerns. This secondary analysis explored the safety and the role of prophylactic G-CSF (proG-CSF) in the delivery of cCTRT. Material and methods: Secondary analysis of 487 patients treated as per protocol on the phase 3 CONVERT trial which randomized patients between once-daily RT or twice-daily. Results: 180 of 487 eligible patients (37 %) received proG-CSF, 60 (33 %) as primary prophylaxis and 120 (67 %) as secondary prophylaxis following myelotoxic events. The regimen incidence of febrile neutropenia (FN) was 22 %. Its incidence in the proG-CSF group reduced significantly when proG-CSF was administered (22 % vs 10 %; OR 0.4; 95 %CI 0.2−0.7; p = 0.002 ). The rate of blood transfusion was higher in the proG-CSF group (51 % vs 31 %; OR 2.4; 95 %CI 1.6–3.5; p < 0.001 ). The incidence of severe thrombocytopenia was also higher is this group (28 % vs 15 %; OR 2.2; 95 %CI 1.4–3.5; p = 0.001 ). But this was significantly higher in those on secondary vs primary prophylaxis (34 % vs 15 %; OR 2.9; 95 %CI 1.3–7.4 p = 0.009 ) No differences observed in RT-related toxicity, treatment-related mortality or any survival outcomes. The optimal dose intensity (85 % or higher) of cisplatin was achieved in more patients within the proG-CSF group (75 % vs 67 %; OR 1.5; 95 %CI 0.9–2.3; p = 0.056 ). Conclusion: There was no evidence that G-CSF directly caused myelotoxicity, instead most patients started G-CSF due to higher myelotoxicity risk. G-CSF maintained the planned dose intensity and there was no detrimental effect on survival. G-CSF may be considered as a supportive measure in this setting.